Apostille Convention and Its Ramification Following the Accession of the Indonesian Legal Practices - David Tan (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2021)
Indonesia has acceded to the 1961 Hague Apostille Convention in early 2021. The government decided the move based on the current endeavors to enhance the quality of civil services, investment rate, government transparency, and recovery efforts after the worldwide pandemic. At the same time, Indonesia’s initiative to accede to the convention is surprisingly unimpressive, considering the benefits for Indonesia due to its urgency. The study reinforces the present perspective of apostille to contribute to the handful of scholarly papers dealing with the apostille in the realm of private international law. This study employed a normative juridical research method with secondary data. The data were analyzed with qualitative analysis methods. This paper examined the issues of the 1961 Hague Apostille Convention from Indonesian perspective and its obstacles in the 21st century. Furthermore, analysis also covered various scientific articles concerning the apostille to increase insight and comprehension of Indonesia’s attempt to accede to the Hague Apostille Convention and the subsequent actions that Indonesia should consider. Finally, this study also highlights the further development for the apostille to avoid deficiencies and vulnerabilities.DOI: https://doi.org/10.22304/pjih.v8n3.a1